2018
DOI: 10.1038/s41598-018-22827-3
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient Cu(In,Ga)(S,Se)2 photocathode without a hetero-materials overlayer for solar-hydrogen production

Abstract: Surface modification of a Cu(In,Ga)(S,Se)2 (CIGSSe) absorber layer is commonly required to obtain high performance CIGSSe photocathodes. However, surface modifications can cause disadvantages such as optical loss, low stability, the use of toxic substances and an increase in complexity. In this work, we demonstrate that a double-graded bandgap structure (top-high, middle-low and bottom-high bandgaps) can achieve high performance in bare CIGSSe photocathodes without any surface modifications via a hetero-materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The detailed fabrication process is presented in our previous work . Briefly, black CIGSSe absorber film was prepared by spin-coating with a paste solution with subsequent heat treatments under sulfurization and selenization atmospheres, resulting in a double band gap graded structure. , CdS buffer and i-ZnO/AZO window layers were deposited onto the CIGSSe films by chemical bath deposition and a sputtering method, respectively. The CIGSSe solar cells showed moderate efficiency of ∼12% under standard illumination (AM1.5 and 100 mW/cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed fabrication process is presented in our previous work . Briefly, black CIGSSe absorber film was prepared by spin-coating with a paste solution with subsequent heat treatments under sulfurization and selenization atmospheres, resulting in a double band gap graded structure. , CdS buffer and i-ZnO/AZO window layers were deposited onto the CIGSSe films by chemical bath deposition and a sputtering method, respectively. The CIGSSe solar cells showed moderate efficiency of ∼12% under standard illumination (AM1.5 and 100 mW/cm 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Photoelectrochemical water splitting and CO 2 reduction using water as an electron donor have gathered much attention as a promising candidate for methodology to convert solar energy to chemical energy. Many efforts have been made to investigate photoelectrochemical properties of Cu-contained compounds, such as sulfides, selenides, and oxides. This is because most of the Cu-containing materials exhibit a p -type semiconductor character that is indispensable for employing them as photocathodes in photoelectrochemical reactions. Among them, it has been reported that Cu-contained metal-sulfide-photocatalyst powders are useful as photocathodes to reduce H 2 O and CO 2 to H 2 and CO, respectively, under simulated solar light. , ,, Moreover, their band gaps correspond to visible light and can be flexibly controlled by the formation of solid solutions. ,,,,, Nevertheless, photoelectrochemical performances of the particulate-based photocathodes are mostly lower than those of the thin films made by vaper deposition ,,, and precursor coating followed by either sulfurization or selenization. ,,,,, A main reason why the performances of the particulate-based photocathodes are lower is considered to be insufficient contacts between the particulate photocatalysts and a conductive substrate such as FTO (fluorine-doped tin oxide). In other words, there are many cavities between the particulates and the FTO.…”
Section: Introductionmentioning
confidence: 99%
“…Copper indium selenide (CuInSe 2 ) has drawn considerable attention for its feasible applications in photovoltaic devices, such as photon absorbers in solar cells, [1][2][3][4] light-emitting diodes, [5][6][7][8] and in biological and catalysis applications. [9][10][11][12] Research on selenide compounds is particularly aimed at securing the controllability of optoelectronic properties with stable chemistry to eventually replace semiconductors that contain toxic elements such as cadmium or lead. [13][14][15] However, because ternary compounds bear inherent complexity in their structure and defect chemistry, 16,17 a full understanding of the role of intrinsic/extrinsic defects in fundamental science is yet to be achieved.…”
Section: Introductionmentioning
confidence: 99%